El proceso de recuperación de la cartera de crédito en la Cooperativa de Ahorro y Crédito San Antonio Cta. Ltda. Sucursal Parroquia La Unión de la provincia de Los Ríos, periodo 2020 – 2021. - Bravo Rivera, Jordán Salomón (2022)
The objective of this case study is the administrative process carried out by the Savings and Credit Cooperative Cta. Ltda. of the Parroquia La Unión for the recovery of the credit portfolio, considering as the main point the administration of the portfolio which consists of the organization, evaluation, monitoring and control of accounts receivable, all this with the purpose of achieving that payments are made in a timely and effective manner. In turn, emphasize various aspects related to the recovery process, such as the requirements, amounts to acquire financing and the type of notification used to recover the portfolio. It should be remembered that for this the characteristics of the client will be analyzed at the time the credit is to be granted, taking into account the socioeconomic level in which they are so that they do not fall behind in payments and also know what type of business who is going to invest the money if the case warrants it, and make them aware of the credit policies of the cooperative. Finally, it is important to mention that in order to obtain the aforementioned data, a field study is required in addition to a bibliographical analysis of the subject in question, in order to have solid bases that allow the construction of conclusions and recommendations oriented to the reality of the company.